(untitled) (Baghdad Science Journal, 2014)
An environmental study conducted on diatoms in Al Yusifiya river beyond its branching from Euphrates river. Four sites were selected along the river for the period from march 2013 to September 2013. The present study involved the measurement of physicochemical parameters, also the qualitative and quantities of diatoms. The studied parameters values ranged as follows: 19-44Cº and 16-30 Cº for air and water temperature respectively, 6.9-8.7, 595-1248 µS/cm, 6.4-8.0 mg/l for pH, electric conductivity and dissolved oxygen respectively. A total of 74 taxa were recorded for diatoms, where the pinnate diatom was the predominant and recorded 64 taxa while 10 taxa for centric diatoms. The total number of diatoms was 1197.55*104 cell /l. The total number values were ranged as follows:( 28.3-48.6) *104 cell /l in the first site ,( 33.6-51.5) *104 cell /l in the second site,( 39.8-67.2) *104 cell /l in the third site and ( 22.3-38.0) *104 cell /l in the fourth site. Two species Asterionellaformosa Hassall and Diploneispuella Schumann were noticed in site 2 only, while C. prostateBerkeleyfound in all studied sites expect in site 1. StephaenodicushantzschiiGrunow and Didymosphenia geminate (lyngb.) Schmidtwere recorded in sites 1 and 3, Anomoeoneissp was recorded in sites 1 and 4 only. The Mastogloiasp was noticed only in sites 2 and 4.